Sales System in the Endocell Mobile Phone Business Using the CRM (Customer Relationship Management) Method) in Kompe Berangin Village, Cerenti District - Ari AP Putra; Erlinda Erlinda; M Yusfahmi (Universitas Islam Kuantan Singingi, 2024)
In order to increase sales and customer service at the Endocell Store in Kompe Berangin Village, this study intends to create a web-based application using a Customer Relationship Management (CRM) methodology. With the use of this application, customers can order products more conveniently, obtain comprehensive product information, and offer feedback and recommendations. The findings of this study produce integrated sales apps that boost client connections, promotions, and operational effectiveness, giving businesses a competitive edge in a crowded market. Customer satisfaction, operational efficiency, and sales performance have all increased with the adoption of web-based apps combined with a CRM strategy. Similar businesses can try to improve their business success by using this solution as a guid.